Corrispondere senza somigliare. La trasformazione come problema filosofico - Pezzano, Giacomo (Philosophy Kitchen - Rivista di filosofia contemporanea, 2017)
The paper discusses the question of isomorphism from a point of view according to which first of all we need to understand the nature of the processes, and thus to consider the phaenomena of transformation as an irreducible philosophical problem. In doing this, I refer to the metaphysical philosophical system of Gilles Deleuze, using and folding some of its main concepts. My principal thesis is that in a transformational perspective talking of “isomorphism” means facing not the question of a correspondence by similarity (adequacy), but that of a correspondence by dissimilarity (adequateness). I discuss such a position in two steps.